2018
DOI: 10.1021/acsami.8b03772
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Rich Porous Polymers for Carbon Dioxide and Iodine Sequestration for Environmental Remediation

Abstract: The use of fossil fuels for energy production is accompanied by carbon dioxide release into the environment causing catastrophic climate changes. Meanwhile, replacing fossil fuels with carbon-free nuclear energy has the potential to release radioactive iodine during nuclear waste processing and in case of a nuclear accident. Therefore, developing efficient adsorbents for carbon dioxide and iodine capture is of great importance. Two nitrogen-rich porous polymers (NRPPs) derived from 4-bis-(2,4-diamino-1,3,5-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 58 publications
(77 reference statements)
5
122
0
Order By: Relevance
“…More recently, Pan et al developed N-and S-rich covalent organic framework (COFs) possessing high iodine uptake of 276 wt.% 29 . Triazine-based conjugated polymers have also been reported to have respectable iodine uptake, presumably due to their nitrogen-rich nature 4,15,[30][31][32][33][34][35] . The high number of basic nitrogen sites on the triazine unit enhances the uptake capacity that originates from the formation of charge-transfer complexes of nitrogen-iodine (donor-acceptor) systems formed during iodine adsorption on the polymers 7,12,15,36 .…”
mentioning
confidence: 99%
“…More recently, Pan et al developed N-and S-rich covalent organic framework (COFs) possessing high iodine uptake of 276 wt.% 29 . Triazine-based conjugated polymers have also been reported to have respectable iodine uptake, presumably due to their nitrogen-rich nature 4,15,[30][31][32][33][34][35] . The high number of basic nitrogen sites on the triazine unit enhances the uptake capacity that originates from the formation of charge-transfer complexes of nitrogen-iodine (donor-acceptor) systems formed during iodine adsorption on the polymers 7,12,15,36 .…”
mentioning
confidence: 99%
“…Radioisotopes 129 I and 131 I are released in exhaust fumes from nuclear power plants. Their capture and storage are a major environmental and public health concern due to their bioaccumulation . The incorporation of heteroatoms such as nitrogen into POPs has enabled the storage and capture of radioactive iodine .…”
Section: Sequestration Of Radioactive Materialsmentioning
confidence: 99%
“…Abdelmoaty et al reported the synthesis of two imino‐based POPs based on 1,4‐bis‐(2,4‐diamino‐1,3,5‐triazine)benzene using terephthalaldehyde (POP‐3) and 1,3,5‐tris(4‐formylphenyl)benzene (POP‐4) (Fig. ) . Vapor‐phase iodine uptake studies revealed maximum iodine uptake capacities for POP‐3 and POP‐4 of 192 and 222 wt%, respectively.…”
Section: Sequestration Of Radioactive Materialsmentioning
confidence: 99%
“…However, their lower removal capacities, poorer stabilities, and tedious synthesis procedures cannot meet the growing industrial demands. Covalently linked porous polymers have been recognized as the most promising adsorbents for the wastewater treatment and CO 2 capture due to their featuring with large surface area, good thermal stability, designable pore structure, and versatile synthetic methods . For example, Tan et al .…”
Section: Introductionmentioning
confidence: 99%